Highly positive-charged zinc(II) phthalocyanine as non-aggregated and efficient antifungal photosensitizer. Issue 11 (1st June 2015) - Li, Xing-Shu; Guo, Jun; Zhuang, Jing-Jing; Zheng, Bi-Yuan; Ke, Mei-Rong; Huang, Jian-Dong
Graphical abstract: Abstract: A new tetra-α-substituted zinc(II) phthalocyanine containing dodeca-amino groups (compound4 ) and its quaternized analogue (compound5 ) have been prepared and evaluated for their photoactivities against Candida albicans . Compared with the dodeca-amino phthalocyanine4, the dodeca-cationic phthalocyanine5 exhibits a higher photodynamic inactivation against C. albicans with an IC90 value down to 1.46 μM, which can be attributed to its non-aggregated nature in aqueous environments and more efficient cellular uptake. More interestingly, 5 shows a higher photodynamic inactivation on C. albicans due to its stronger affinity to C. albicans cells than mammalian cells. These results suggest that the highly positive-charged phthalocyanine5 is a potential non-aggregated antifungal photosensitizer, which shows some selectivity toward the fungus.